Changes in the Pathway of Ethylene Production Following Citrus Exocortis Viroid Infection in Tomato Plants - Belles, Jose M.; Durán-Vila, Núria; Conejero, Vicente (IOCV, 2021)
Ethylene production was stimulated during the systemic reaction of Rutgers tomato to citrus exocortis viroid (CEV) infection. The increase in ethylene production of CEV-infected leaf discs was parallel to the increase in 1-aminocyclopropane-1-carboxylic acid (ACC) production, and content. Moreover, the capacity to convert ACC into ethylene (ethylene forming enzyme activity) in CEV-infected leaves also increased. The blockage of ACC synthase with aminooxyacetic acid (AOA) completely prevented the viroid-induced production of ethylene, thus indicating that this enzyme is the primary controlling step of ethylene biosynthesis acted upon in viroid infection. The increased ethylene-forming enzyme (EFE) activity acts as a secondary contributor to the enhanced production of ethylene.